Episteme vs. Tekné: an approach to the learning of computer programming in Systems Engineering (2019)
This article exposes the results of a research made in the classroom looking for establishing elements of comparative judgment that would allow comparing two teaching strategies, and their impact on learning, of computer programming in a Systems Engineering program. The two strategies to be compared consist of the teaching of the logic of programming (the episteme) or the teaching of its application reflected in a programming language (tekné). In order to measure the impact of the two strategies on the learning of programming, Programming I courses were divided into two subgroups so that a comparative follow-up could be carried out permanently. The process was carried out with the 1st semester of Systems Engineering of a public university. The results were measured quantitatively from identical written evaluations and under highly similar conditions for their resolution. A qualitative approach was also made based on the opinion of the students at the end of the course. It is concluded that the teaching of the episteme of programming seems to be much more relevant than its application since the student can go from the 1st to the other. However, there were cases in which some students, from the study of the programming language, were able to infer the underlying concepts of the relevant logic.